Analisis Politik Intermediary: Fungsi Partai Politik di Pemilihan Calon Tunggal - Moh Maskurudin Hafid (Syntax Idea)
Political parties play a central role in nominating regional head candidates to ensure voter representation in elections. The broader the representation in the electoral process, the higher the level of democracy and legitimacy achieved. However, in the 2024 Regional Elections (Pilkada), despite the relaxation of nomination requirements, the number of competing candidate pairs remains limited. According to the Constitutional Court (MK) ruling, each region should ideally have at least five candidate pairs, yet in reality, more than half of the regions were contested by only two or three pairs, with 37 regions having a single candidate running unopposed. This study aims to map the coalition of political parties in regions with single candidates and analyze the extent of political party involvement in the nomination process. The research employs representation analysis, examining the number of political parties supporting candidate pairs, the origin of candidate pairs' parties, and the nomination threshold. The findings indicate that, in many cases, political parties tend to form broad coalitions supporting a single candidate rather than fostering greater competition. This phenomenon reduces voter choices and weakens electoral competition at the regional level. As an implication, this study provides insights for policymakers to reevaluate nomination regulations to encourage healthier and more democratic political competition in regional elections.